2012
DOI: 10.1111/j.1468-232x.2012.00702.x
|View full text |Cite
|
Sign up to set email alerts
|

What Makes Workers Happy? Anticipated Rewards and Job Satisfaction

Abstract: Using data collected from over 9400 employees in Armenia, Kazakhstan, Kyrgyzstan, Russia, and Serbia, across a wide variety of workplaces and sectors, we identify the extrinsic and intrinsic rewards that workers desire and expectations of receiving these rewards. We use ordered probit regression analysis to evaluate the association between anticipated rewards and job satisfaction, hypothesizing that reward desirability matters most for extrinsic rewards linked to numeric values. Data strongly support our hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 84 publications
2
68
0
Order By: Relevance
“…Respondents were required to assess their perceptions regarding AWC using a 5-point Likert-scale (1 = not good; 2 = slightly good; 3 = somewhat good; 4 = very good; and 5 = extremely good). Examples of the type of incentive item are listed in Table 1 [17,29]. The same items were used to assess the respondents’ DWC (see Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Respondents were required to assess their perceptions regarding AWC using a 5-point Likert-scale (1 = not good; 2 = slightly good; 3 = somewhat good; 4 = very good; and 5 = extremely good). Examples of the type of incentive item are listed in Table 1 [17,29]. The same items were used to assess the respondents’ DWC (see Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…The crowding-out effect proposes that extrinsic rewards have a negative impact on intrinsic motivation [28]. Previous researches have suggested that both desired workplace incentives and perceived actual incentives affect job satisfaction, either directly or indirectly [23,29]. For example, Linz and Semykina assessed the relationship between job satisfaction and anticipated reward [29].…”
Section: Introductionmentioning
confidence: 99%
“…Linz and Semykina [5] revealed that personal income is positively correlated to job satisfaction. A study of Taiwan R&D professionals in technology sector found out that monetary incentives based on output has a positive relationship with their work performance.…”
Section: Extrinsic Rewardmentioning
confidence: 99%
“…They also contend that healthy workplace provides all members of the workforce with physical, psychological, social and organizational conditions that protect and promote health and safety. They also affirm that it enables managers and workers to increase control over their own health and to improve it, and to become more energetic, positive and contented (Sparks et al2001;Burton, 2010;Dibben & Williams, 2012;Linz & Semykina, 2012;Snape&Redman, 2012).…”
Section: Management's Response To Problems Of Industrial Relations Inmentioning
confidence: 99%